Simulation of the Human Footsteps Induced Floor Vibrations - Claesson,Jimmy (TVBA, 2008)
How people walk is very individual and even their personal style of walking may change throughout their lives. But it could be that the people of the same sex with the same height, weight and age would have a way of walking with great similarities in terms of feet angle and length of the stride. This project examined the geometric walking pattern experimentally of 150 men between 170 and 190 cm. Each of the subjects had to walk with paint on their feet, a three-metre long stretch of paper. From the walking pattern that was created on paper the values of a number of variables was extracted and examined statistically. These data were divided into 5 groups to investigate the link with height. The 5 groups were 170-175, 176-180, 181-185, 186- 190 and the entire sample. The results of the survey were that the variables that describe the walking pattern can be divided into two separate groups, those who have a connection with the height and those who do not. The characteristics that have a connection to the height are the ones that work in the direction that the person is walking. However, these variables are probably not linked to the whole body, but only length of the legs of the person. The variables that are not connected to the height has to do with the width of walking pattern and this is probably linked to the width of the pelvis. From all this statistical data a number of Marko chains was constructed that described the change in the variable value from stride to stride. These would be used to examine if it was possible that, instead of using the conventional method of calculating the amount of sound that is transmitted because of footsteps, take advantage of a simulation with the finiteelement method and investigate the transmission in a computer. The FEM-simulation that was carried out showed that it is possible to simulate walking on the floor in a computer and calculate vibrations so that it is possible to evaluate the different structures and to avoid the worse ones.
Keywords: Markov chains; Stride; Walking pattern; FEM; Vibrations